Social determinants of tuberculosis in Nigeria: an ecological approach - Olusoji Daniel; Olusola Adejumo; Janet Bamidele; Adekunle Alabi; Abiola Gbadebo; Kolawole Oritogun (AOSIS, 2022)
Background: Nigeria is 4th among 22 tuberculosis high-burden countries. However, TB is not evenly distributed in the country, presumably due to state-specific risk factors. Objectives: This study maps TB and socioeconomic risk factors in Nigeria. Methods: State-level age/sex standardized tuberculosis notification data was utilized in an ecological design to evaluate the spatial distribution of TB in Nigeria and its social and economic consequences between 2012 and 2015. Negative binomial regression analysis examined the relationship between TB and five state-level covariates: HIV, BCG coverage, GDP per capita, percentage underweight, and percentage treatment success rate. Global and Local Moran's I test statistics in R were used for spatial analysis. Results: The mean age/sex TB CNR was 54.4/100,000. Non-spatial ecological regression analysis found that TB was greater in states with high HIV, low BCG, low GDP per capita, and low TB death rates. Three states-Nasarawa, Benue, and Taraba-had high TB rates and spatially auto-correlated TB CNRs. Conclusions:  TB case notification differed by age and gender. Economically-disadvantaged states exhibited higher TB case notification, HIV prevalence, lower BCG coverage, and lower mortality rates. The study found three TB hotspots. To reduce the national TB notification rate discrepancy, TB policies should incorporate social variables and target high-risk states with specific initiatives.